Comparison of the effectiveness of colloidal oatmeal 1% with petrolatum 100% to repair the skin bars in psoriasis vulgaris: A study of trans-epidermal water loss - Riyanto, Puguh; Sugianto, Yosep Ferdinand Rahmat; Z, Mutia Dian Permatasari Mochtar (Institute of Computer Science (IOCS), 2025)
The purpose of this study was to compare the effectiveness of 1% colloidal oatmeal with 100% petrolatum in improving the skin barrier in patients with psoriasis vulgaris. This research method is a randomized, single-blind, pre and posttest design controlled trial involving patients with mild/moderate/severe psoriasis vulgaris at DR. Kariadi Hospital Semarang, Indonesia. The subjects of the study were divided into 2 groups, namely 1% colloidal oatmeal and 100% petrolatum. Evaluation was carried out by comparing the TEWL values between day 0 and day 28. The analysis was carried out using independent T-tests, Mann Whitney, and Wilcoxon. The results were significant if p<0.05 Results Topical administration of 1% colloidal oatmeal or 100% petrolatum could lower the TEWL value in each study group (p<0.001; p=0.006 respectively). ΔTEWL evaluation showed a significantly greater decrease in TEWL in the 1% colloidal oatmeal group (p=0.003). No complaints during use were reported in the 1% colloidal oatmeal group. Conclusion: Topical application of 1% colloidal oatmeal is more effective than 100% petrolatum as a moisturizer in improving the skin barrier in patients with psoriasis vulgaris without complaints.